Cold Plasma-Induced Surface Modification of Microfibrillated Cellulose Using Lauric Acid to Enhance Compatibility in Polymer Composites - Rifathin, Annisa; Wijaya, Ade Mundari; Roziafanto, Achmad Nandang; Laksmono, Joddy Arya; Nugraha, Adam Febriyanto; Chalid, Mochamad (Universitas Gadjah Mada, 2025)
Green materials, such as microfibrillated cellulose (MFC), are increasingly used as fillers in polymer composites for academic and industrial applications. However, their inherent hydrophilic property limits compatibility with polymer matrix. This study employs an environmentally friendly cold plasma technique to modify the surface of MFC, improving its compatibility with the polymer. Plasma treatment was performed at a voltage of 60 V for 30 min by making three molar ratios (3:1, 4:1, and 5:1) between lauric acid as a hydrophobic precursor and anhydroglucose (AGU). The results indicate several changes in the modified MFC properties, as evidenced by the appearance of a new peak at a wavenumber of 1742 cm−1 (ester’s C=O) in FTIR spectra, indicating successful plasma-induced grafting. XPS results also confirm the formation of O–C=O bond at a binding energy of 289.3 eV. The optimum conditions were obtained at a molar ratio of 4:1 (lauric acid:AGU). There was a decrease in the hydrophilic property of MFC, indicated by an increase in the water contact angle from 50.16° to 71.26°. Moreover, the surface tension difference between MFC and polypropylene was significantly reduced from 136.99 to 47.51%, suggesting improved compatibility.